Aprendizajes significativos e inteligencias múltiples en la asignatura de Química. Año lectivo 2021-2022. - Alvarado Guaillas, Kevin Augusto (2022)
The implementation of multiple intelligences in the classroom is relevant, it gives the student the ability to know the best ways to acquire significant learning, improving the Teaching and Learning process TEP. The objective of the research is to generate significant learning in students, through the implementation of methodological strategies that enhance multiple intelligences in the subject of Chemistry, first year of BGU, school year 2021-2022, thirty-eight students were part of the study sample, they belong to parallel "E" of "Bernardo Valdivieso" High School. The methodology corresponds to the qualitative method, the level of research is of field work and participatory action; it allows to obtain data directly with the researched subjects; in the same way, it is supported by documentary research, it is based on bibliographical research, which helps us to implement strategies in the classroom; and, finally, it is transversal, since the research was carried out in a short period of time with the purpose of improving the TEP. The results of the research are supported and presented based on the bibliographic review mainly on multiple intelligences, significant learning, and curriculum of the chemistry subject. In addition, tabulated graphs are presented with the respective data of the empirical research and its reading for better understanding; finally, the contrast of theory with the reality found in the selected sample. Concluding that teachers prepare and execute homogeneous classes in the classroom, hence, in the intervention proposal, it was found that considering multiple intelligences, through strategies according to their reality and different techniques, to enhance the types of intelligences; student learning was strengthened, improving the classroom climate and achieving significant learning. Keywords: Teaching-learning, significant learning, teaching strategies, Intelligence types.